Fully automated synthesis and coupling of [18F]FBEM to glutathione using the iPHASE FlexLab module. (7th January 2014) - Ackermann, Uwe; Plougastel, Lucie; Wichmann, Christian; Goh, Yit Wooi; Yeoh, Shinn Dee; Poniger, Stan S.; Tochon‐Danguy, Henri J.; Scott, Andrew M.
<x xml:space="preserve">Abstract</x> Site‐specific radiolabelling of peptides or antibodies using [18F]FBEM is often preferred over non‐site‐specific radiolabelling with [18F]SFB because it does not affect the affinity of the antibody to its target. Unfortunately, the synthesis of [18F]FBEM and its conjugation to thiol containing macromolecules requires some manual intervention, which leads to radiation exposure of the radiochemist. In this publication, we report on the complete automation of [18F]FBEM production and its subsequent conjugation to glutathione using a slightly modified iPHASE FlexLab module. [18F]FBEM was produced in 1.185 ± 0.168 GBq (15–20%; n = 10; 0.75 ± 0.106 GBq non‐decay corrected) with a specific activity of 57 ± 10 GBq/µmol. Radiochemical purity was 97 ± 1% and the synthesis time including HPLC purification and reformulation was 70 min. After evaporation to dryness, [18F]FBEM was conjugated to glutathione in PBS buffer pH 7.4 in quantitative yields. This fully automated method does not require any manual intervention and therefore reduces the radiation exposure to the operator.